TEACHERS EXPLORE: QUESTIONING SKILLS IN ENGLISH LANGUAGE TEACHING - Saputra, Rizky Imam (Universitas Negeri Medan, 2024)
Effective questioning skills are essential for successful English teaching. Questioning skills are one of the important competencies that English teachers must have to support effective learning. This research took the title